ANALISIS DAN USULAN PERBAIKAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DENGAN METODE HIRARC DAN FTA PADA PT POLA GONDOLA ADIPERKASA - Muhamad Noval Prabowo (2022)
PT. Pola Gondola Adiperkasa is a company that operates as a Safe Lifting Specialist who sells and rents gondolas. The amount of productivity makes the company experience many obstacles that occur. Work problems that exist at PT. The Adiperkasa Gondola pattern is that 53% of work accidents occur in the construction section which can cause physical defects in the workers' body parts and decrease work productivity. To reduce the causes of work accidents in the construction section, an evaluation of SMK3 is carried out, identification of hazards and dealing with causes of work accidents. Identification of the potential (source) of this hazard is done by recording all the steps for each activity that occurs in the construction division at PT. The Adiperkasa Gondola pattern uses a risk management stage approach or Hazard Identification, Risk Assessment, Risk Control (HIRARC) so that a total of 22 risk events are obtained. Potential hazards that have the highest Risk Priority Index (RPI) category are 15 risk events, then 7 risk events to find the cause of risk events with Fault Tree Analysis. Recommendations according to potential hazards are to design a prototype overload warning system, use personal protective equipment (PPE), supervise the implementation of work activities, train and carry out routine inspections on gondola machines. So that the results obtained from the causes of work accidents are expected to reduce the level of work accidents that exist from previous accidents by using the HIRARC and FTA methods